Gas transmission networks in Europe: Connections between different entry-exit tariff methodologies. (1st September 2016) - Bermúdez, Alfredo; González-Díaz, Julio; González-Diéguez, Francisco J.; González-Rueda, Ángel M.
Highlights: This paper presents a discussion of different methodologies for computing entry-exit tariffs. Explicit formulas for the computation of two of the main methodologies are derived. It is shown that, after a natural adjustment, they coincide. An important issue about the use of weighted or unweighted methodologies is discussed. The findings are illustrated on an example and the policy implications are discussed. Abstract: Following a request of the European Commission in 2012, different bodies within the gas energy sector have been working on a Network Code for transmission tariffs. The final goal is to get a more harmonized structure within the European Union. This paper complements those efforts by developing a formal treatment of some methodological aspects arising in past and present drafts of the Network Code. First, the analysis provides simple formulas for the computation of the tariffs resulting from the application of two of the main methodologies that have been discussed in the official documents: the capacity-weighted distance approach and the least squares approach. Second, it is shown that the tariffs delivered by the two approaches are perfectly correlated with each other. Maybe more importantly, if a natural adjustment is performed to control tariff dispersion, then both approaches lead to exactly the same tariffs. Moreover, the analysis highlights an issue that may have been overlooked by regulators and also by past publications: the difference between weighted and unweighted versions of the methodologies under study and the reasons why weighted versions should be preferred. The paper concludes with a brief comparison with other methodologies and discussing some policy implications.